The Effect of Innovation in Waste Management and Sustainable Packaging on Perceived Value and Consumer Satisfaction in the Snack Food Industry in East Java - Mohammad Gifari Sono; Budi Sulistiyo Nugroho; Weni Indah Doktri Agus Tapaningsih; Yendri Deswin (West Science Social and Humanities Studies, 2024)
This study investigates the impact of waste management innovation and environmentally friendly packaging on perceived value and consumer satisfaction in the snack food industry in East Java. Utilizing a quantitative approach, data were collected from 170 respondents using a Likert scale (1-5). The analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings reveal that both waste management innovation and sustainable packaging positively affect perceived value and consumer satisfaction, with sustainable packaging having a stronger influence on satisfaction. Additionally, perceived value mediates the relationship between sustainability initiatives and consumer satisfaction. These results underscore the importance of adopting visible and impactful sustainability practices to enhance customer perceptions and loyalty. Snack food manufacturers are encouraged to prioritize eco-friendly packaging while communicating the broader benefits of waste management innovations to consumers.